1997
DOI: 10.1177/152574019701900103
|View full text |Cite
|
Sign up to set email alerts
|

What is required for transition from the ESL classroom to the general education classroom? A case study of two classrooms

Abstract: Speech-language pathologists in the schools and classroom teachers repeatedly face the challenge of how best to provide services and instruction for students who are learning English as a second language (ESL). A better understanding of second language acquisition issues, such as code-switched and code-mixed behaviors, is essential because, as Aguirre (1989) maintains, code switching is obvious and unavoidable with bilingual students. An ethnographic observational study of ESL and regular classroom discourse w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…Analysis revealed that 18% (448/2,454 words) of the facilitator's language was spoken in Spanish. This is comparable to the 17.4% figure found by Brice and Perkins (1997) when bilingual teachers spoke with bilingual students in classrooms. Therefore, it appears that the facilitator offered ample opportunities for the students to speak in both languages.…”
Section: Data Collectionsupporting
confidence: 79%
“…Analysis revealed that 18% (448/2,454 words) of the facilitator's language was spoken in Spanish. This is comparable to the 17.4% figure found by Brice and Perkins (1997) when bilingual teachers spoke with bilingual students in classrooms. Therefore, it appears that the facilitator offered ample opportunities for the students to speak in both languages.…”
Section: Data Collectionsupporting
confidence: 79%
“…Spontaneous language use. The SLP should ' allow the children to code switch and code mix when it facilitates spontaneous language use (Brice & Perkins, 1997). Children who code switch are dependent on the community's acceptance to use of this form of communication (Kayser, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The code-mixed combination of English and the native language (e.g., Spanish) constitutes a unique third language form (Brice & Perkins, 1997;Heller, 1988). We argue that language alternation (particularly code mixing) may indicate a sophisticated user who, with appropriate input, time, and practice, exhibits sound cognitive and linguistic functioning.…”
Section: Types Of Language Alternationmentioning
confidence: 99%
See 1 more Smart Citation
“…He has been listening and speaking English for approximately 2 years. Miguel was observed as part of an ethnographic study reported elsewhere (Brice & Perkins, 1997). However, information from his experiences in the general classroom shall be reported here.…”
Section: Case Studymentioning
confidence: 98%